SOCIAL MEDIA AS A MEANS OF INTERACTION FOR IDDAH AND IHDAD WOMEN PERSPECTIVE ON THE BOOK OF I’ANATUTTHOLIBIN - Jannah, Roiha; Ainiyah, Qurrotul (Universitas Islam Negeri Ar-Raniry, 2024)
Islam prohibits women from leaving the house and dressing up during the iddah and ihdad periods, anticipating freedom of interaction which will lead to mafsadat. However, the reality in society is that social media is now used as a means of interaction that makes it easier for users not to leave the house. Addressing this issue, the author explores the thoughts of Sayyid Abu Bakar Utsman bin Muhammad Syatha’ ad-Dimyathi through his book I'anatutthilibin. This research uses qualitative methods (library research). With results 1. The law on using social media as a means of interaction is not permitted because it is equated with a prohibition on leaving the house. However, the law becomes permissible if there is something that is unlawful in its implementation. 2. In the context of this problem, Sayyid Abu Bakar Utsman bin Muhammad Syatha’ ad-Dimyathi opinion can be applied by looking at the flaws in being able to leave the house for the reason of prioritizing the benefit of human life.